2006
DOI: 10.1117/12.680967
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of physical properties of particulate emission from animal feeding operations using three-wavelength elastic lidar measurements

Abstract: Agricultural operations produce a variety of particulates and gases that influence ambient air quality. Lidar (LIght Detection And Ranging) technology provides a means to derive quantitative information of particulate spatial distribution and optical/physical properties over remote distances. A three-wavelength scanning lidar system built at the Space Dynamic Laboratory (SDL) is used to extract optical parameters of particulate matter and to convert these optical properties to physical parameters of particles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The statistical analysis of measurement accuracy (absolute error or bias with respect to the true value), measurement uncertainty (root mean square RMS error with respect to the true value), and measurement precision (standard deviation estimated with respect to the mean sample value) were estimated for 50 runs for each aerosol type and condition. Simulations were also conducted with a form of the retrieval algorithm [21] that permitted the retrieval of unconstrained solutions. For the single-mode log normal particle size distribution under the different scenarios of unconstrained parameters of particle size distribution, fixed mode radius (µ-constrained), and fixed width of the distribution ( -constrained), it was found that the unconstrained solution had significantly more error than the fully-constrained solution.…”
Section: Aerosol Model Sensitivity Analysismentioning
confidence: 99%
“…The statistical analysis of measurement accuracy (absolute error or bias with respect to the true value), measurement uncertainty (root mean square RMS error with respect to the true value), and measurement precision (standard deviation estimated with respect to the mean sample value) were estimated for 50 runs for each aerosol type and condition. Simulations were also conducted with a form of the retrieval algorithm [21] that permitted the retrieval of unconstrained solutions. For the single-mode log normal particle size distribution under the different scenarios of unconstrained parameters of particle size distribution, fixed mode radius (µ-constrained), and fixed width of the distribution ( -constrained), it was found that the unconstrained solution had significantly more error than the fully-constrained solution.…”
Section: Aerosol Model Sensitivity Analysismentioning
confidence: 99%
“…The details of our lidar calibration and aerosol retrieval process are discussed in detail by Marchant [19] and Zavyalov [11]. The lidar return power from range z for a single scatter is shown in (1).…”
Section: Lidar Retrieval Calibrationmentioning
confidence: 99%
“…The algorithm used to retrieve aerosol physical parameters from a raw Aglite lidar signal shown schematically in Fig. 3B involves four major steps [11] [21], which account for the geometrical form factor of the telescope receiving optics and scattered sunlight background radiation. The routine then calculates the optical parameters (backscatter and extinction coefficients) of the background and source aerosols at three wavelengths.…”
Section: Lidar Retrieval Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of retrieving aerosol mass concentration from the Aglite lidar data is discussed in details in our previous publications [6,10]. The retrieval process can be summarized as following (see Figure 2).…”
Section: Lidar Mass Concentration Retrievalmentioning
confidence: 99%